MENDALAMI LIVING QUR'AN: ANALISIS PENDIDIKAN DALAM MEMAHAMI DAN MENGHIDUPKAN AL-QUR'AN: EXPLORING THE LIVING QUR'AN: AN ANALYSIS OF EDUCATION IN UNDERSTANDING AND LIVING THE QUR'AN. - Murtadlo, Ghulam; Khotimah, Anggrayny Khusnul; Alawiyah, Dina; elviana, elza; Nugroho, Yanwar Cahyo; Ayuni, Zulfi (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2023)
The idea of a living Qur'an and the role of education in understanding and bringing the Qur'an to life are the subjects of this study.  The study of the Qur'an includes more than textual interpretation and analysis; it also includes social phenomena related to the day-to-day presence of the Qur'an, or "the living Qur'an."The study used qualitative methodology and literature review.  In order to understand the idea of the living Qur'an and its educational function, information is drawn from various sources, among others as books, articles, and previous research. The results show how important the living Qur'an is to modern Qur'anic research.  It describes the Qur'an as a dynamic part of society intertwined with daily customs, social norms, and cultural activities.  By encouraging the application of Qur'anic values in daily activities and offering a more comprehensive view of the context of the Qur'an and its practical application, education plays an important role in understanding and actualizing the Qur'an. In short, The Living Qur'an offers an interesting substitute for the study of the Qur'an.  A deeper and more relevant understanding of the Qur'an and the application of its principles in everyday life can be fostered by incorporating education into the understanding of the Qur'an in social and real-world contexts.